Upaya Humas Radio Republik Indonesia Banten Dalam Mempertahankan Eksistensi Lembaga - Ida Farida; Noerma Kurnia Fajarwati; Meiby Zulfikar; Rizqi Fitrianti; Arfian Suryasuciramdhan (Pusat Riset dan Inovasi Nasional, 2026)
This study analyzes the public relations efforts of Radio Republik Indonesia (RRI) Banten in maintaining its existence in the digital era and identifies the inhibiting factors faced. Using a qualitative method with a case study approach, this research involved in-depth interviews with informants from various divisions at RRI Banten, as well as observations of the communication strategies and programs implemented. The results of the study indicate that RRI Banten has undertaken a significant digital transformation, including through the development of the RRI Digital application as a means to expand broadcast access, active use of social media to reach a wider audience, and the implementation of a broadcast program segmentation strategy to adapt to the needs and preferences of listeners from various groups. However, the study also identified several crucial inhibiting factors. Limited human resources, particularly in mastery of digital technology, remain a major obstacle in optimizing the transformation program. In addition, the uneven geographic coverage of broadcasts in some areas limits public access to RRI services. Increasingly fierce competition with other digital media that offer greater flexibility, speed, and interactivity also poses a major challenge. On the other hand, the lack of optimal digital promotion and difficulties in reaching the interests of the younger generation hamper the increase in RRI's popularity in the era of media digitalization.